Nuclear factor I and mammary gland factor (STAT5) play a critical role in regulating rat whey acidic protein gene expression in transgenic mice. - Li, S (1995)
The rat whey acidic protein (WAP) gene contains a mammary gland-specific and hormonally regulated DNase I-hypersensitive site 830 to 720 bp 5' to the site of transcription initiation. We have reported previously that nuclear factor I (NFI) binding at a palindromic site and binding at a half-site are the major DNA-protein interactions detected within this tissue-specific nuclease-hypersensitive region. We now show that point mutations introduced into these NFI-binding sites dramatically affect WAP gene expression in transgenic mice. Transgene expression was totally abrogated when the palindromic NFI site or both binding sites were mutated, suggesting that NFI is a key regulator of WAP gene expression. In addition, a recognition site for mammary gland factor (STAT5), which mediates prolactin induction of milk protein gene expression, was also identified immediately proximal to the NFI-binding sites. Mutation of this site reduced transgene expression by approximately 90% per gene copy, but did not alter tissue specificity. These results suggest that regulation of WAP gene expression is determined by the cooperative interactions among several enhancers that constitute a composite response element.